Enhancements in Smart Application for Tracking Farm Land Using Cloud Computing - J., Rajeswari; J. P., Josh Kumar; Nair M., Saranya; R., Ratheesh; S., Navaneethan; K., Elaiyarani; B., Shanmugam (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Smart farming is a renovation in the agriculture sector that focuses on information and communication technologies employed in machinery, equipment, and network-based sensors. Invasive pests are estimated to cost at least $70 billion per year and contribute to the loss of biodiversity, which is reported by the Food and Agriculture Organization of the United Nations (FAO). In this proposed study, a prototype of device was developed with a smart application to help farmers by monitoring their farmland's temperature, air humidity, soil wetness, and lighting. The user can utilize the options provided by the application to decide what has to be done on the field, such as providing water or pesticides, while keeping a watch on the real-time data for soil moisture, temperature, humidity, and plant height (to determine the harvest time). Additionally, the automatic motor on and off control has been included in this prototype, which helps to water the fields at the right time. The Open Weather API, JSON, XML, HTML, and relay modules are the methods utilized to develop smart applications. Mechanisms such as cloud computing and the IoT (Internet of Things) were used to develop this proposed method. Moreover, the sensors, mobile applications, and big data analytics were also utilized to support the enhancements in smart farming. This strategy yields advanced monitoring and increased agricultural productivity.